Deep brain stimulation of the subthalamic nucleus and cognitive functions in Parkinson's disease - Klempírová, O; Jech, R; Urgosík, D; Klempír, J; Spacková, N; Roth, J; Růzicka, E (Prague medical report, 2007)
Deep brain stimulation of the subthalamic nucleus (DBS/STN) is an effective treatment for motor symptoms in advanced Parkinson's disease (PD). However, it is less clear how DBS/STN affects cognitive functions. We investigated 19 PD patients (13 male, 6 female, mean age 57 +/- 6, mean PD duration 15 +/- 4 years) who received bilateral DBS/STN. Neuropsychological assessment was done before the surgery and at least 12 months after DBS implantation. The patients were examined in their optimal motor status. Global cognitive performance measured by Mattis Dementia Rating Scale was not significantly changed after DBS STN. The performance in Wechsler Memory Scale III decreased in the subtest Logical Memory, in delayed recall (p < 0.05) and in recognition (p < 0.05). In Stroop Test, the performance worsened in the second (p < 0.05), and third condition (p < 0.01) measuring interference and ability to suppress automatic reactions. In conclusion, patients treated by DBS/STN tend to worsen in executive functions and in logical memory.
Keywords: Cognition; Memory; lidé; Deep Brain Stimulation; hluboká mozková stimulace; Middle Aged; mužské pohlaví; paměť; Subthalamic Nucleus; kognice; Parkinsonova nemoc; ženské pohlaví; neuropsychologické testy; Humans; Parkinson Disease; lidé středního věku; nucleus subthalamicus; Female; Neuropsychological Tests; Male